Expoentes de escala para mapeamentos discretos bidimensionais - Penalva, Julia [UNESP] (2014)
A transition from integrability to non-integrability in a set of two-dimensional, nonlinear and area preserving mappings that exhibit mixed phase space is characterized in this work. The phase space of the mappings present an extense chaotic sea surrounding a set of establity islands and is limited by a set of invariant spanning curves. The description of the transition from integrability to nonintegrability is made using scaling functions for average quantities in the phase space along the chaotic sea. The critical exponents are obtained by large scale simulations. A connection to the standard map is established as an analytical approximation for the critical exponents